VISUAL OUTCOME AND COMPLICATIONS OF PEDIATRIC CATARACT SURGERY AT LUMBINI EYE INSTITUTE, NEPAL - Thapa, Hari Bahadur; Rai, Salma KC; Bhari, Arjun Malla; Bassett, Ken (Journal of Universal College of Medical Sciences, 2016)
INTRODUCTION: Pediatric eye care, including cataract surgery, has become much more common in Nepal in recent years in tertiary facilities such as the Lumbini Eye Institute (LEI). This study provides the first report of visual outcome and complications after cataract surgery at that Institute. MATERIAL AND METHODS: This is a prospective observational study of all cataract surgical patients <16 years of age between March 1, 2011, and February 28, 2012. Visual outcome was assessed by two optometrists with pediatric eye care training. Clinical data were gathered in a specifically designed pediatric eye program database and demographic data were taken from hospital administrative records. RESULTS: In 2011-12, 334 children (248 boys [74%]) underwent cataract surgery, including 89 Nepali (27%) and 245 Indian (73%) children. In total, 320 (96%), 270 (81%), and 190 (57%) attended their first, second and third follow up visits respectively. Pre-operative visual acuity was <6/60 (91%), 6/60 to <6/18 (7%) and >6/18 (2%). Post-operatively, visual acuity was <6/60(27.5%), 6/60 to <6/18 (36.5%) and 6/18 or better (36%). The mean best corrected visual acuity was 6/38 first follow up, 6/34 second follow up, and 6/30 third follow up. Intraoperative complications were 1.6% pupillary capture and post-operative complications were 35.3% posterior capsular opacification (PCO). CONCLUSION: For 63% of children, visual acuity significantly improved with cataract surgery beyond their presenting vision of <6/60, with over 38% of children achieving visual acuity (>6/18). Follow up beyond one month needs significant improvement to treat postoperative complications particularly posterior capsular opacification. Journal of Universal College of Medical Sciences (2015) Vol.03 No.02 Issue 10 Page: 35-38